RESPON TERHADAP BAKU KEBISINGAN BUNYI DENGAN PENEKANAN PADA SOUNDSCAPES DI PUSAT KOTA. STUDI KASUS KAWASAN TKB DI KOTA MANADO (RESPONSE TO THE STANDARD NOISE WITH EMPHASIS ON SOUNDSCAPES IN THE CENTER TOWN. A CASE STUDY OF THE AREA OF TKB IN MANADO) - Suriandjo, Hendrik S.; Tondobala, Linda (MEDIA MATRASAIN, 2013)
Standard noise in Indonesia is about the noise level in the living environment and based on the Decree of the Minister of Environment No. Kep-48/Menlh/11/1996. Acoustics soundscapes is part of the living environment that put emphasis on the quality of the sound perception by people. The purpose of this study to determine the amount of the value of sound-level for the comfort of the public open space in urban areas. It will be then be proposed as new standard of sound comfort in RTNH (Non Green Open Space) in the city center. The study has aim also to discover the benefits of soundscapes as a tool of analysis in the design of the city. The experiment was conducted in center-town of Manado (TKB area). The study apply mix methods, measurements with a sound level, and descriptive analysis by using qualitative and quantitative approaches. Calculations also realized by applying formula LAeq (10 minutes) and Leq (afternoon), to get the standard limit noise of the area. The results showed that the response of people feel comfortably in the range of 55 to 60 dBA. These values may reach of 20% higher than as mentioned in the standard noise level in Indonesia (Kep-48/Menlh/11/1996). Moreover, it can be justified that soundscapes can be used as tool in the analysis of urban design, especially in the search for the meaning of places.Key Word : standard outdoor noise, response, soundscapes, public open space